(untitled) (Journal of Health, Population and Nutrition, 2009)
Bangladesh has maintained a low HIV prevalence (of less than 1%) despite multiple risk factors. However, recent serological surveillance data have reported very high levels of HIV infection among a subgroup of male injecting drug-users (IDUs). This suggests that an HIV/AIDS epidemic could be imminent in Bangladesh. Although biomedical and behavioural change projects are important, they do not address the root causes of observed risky behaviours among ‘high-risk’ groups. In Bangladesh, these groups include sex workers, IDUs, males who have sex with males, and the transgender population-hijra-who are all excluded groups. Using a social exclusion framework, this paper analyzed existing literature on HIV in Bangladesh to identify social, economic and legal forces that heighten the vulnerability of such excluded groups to HIV/AIDS. It found that poverty and bias against women are major exclusionary factors. The paper presents areas for research and for policy action so that the social exclusion of high-risk groups can be reduced, their rights protected, and an HIV epidemic averted. Key words: Acquired immunodeficiency syndrome; Gender issues; HIV; Homosexuality; Needle-sharing; Sex behaviour; Social exclusion; Stigmatization; Bangladesh doi: 10.3329/jhpn.v27i4.3404 J Health Popul Nutr 2009 Aug;27(4):587-597